Retinal optical coherence tomography features associated with incident and prevalent parkinson disease - Wagner, SK; Romero-Bascones, D; Cortina-Borja, M; Williamson, DJ; Struyven, RR; Zhou, Y; Patel, S; Weil, RS; Antoniades, CA; Topol, EJ; Korot, E; Foster, PJ; et al. (American Academy of Neurology, 2023)
Background and Objectives: Cadaveric studies have shown disease-related neurodegeneration and other morphological abnormalities in the retina of individuals with Parkinson disease (PD); however, it remains unclear whether this can be reliably detected with in vivo imaging. We investigated inner retinal anatomy, measured using optical coherence tomography (OCT), in prevalent PD and subsequently assessed the association of these markers with the development of PD using a prospective research cohort.